2011
DOI: 10.1093/arclin/acr090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Embedded Malingering Indices in a Non-Litigating Clinical Sample using Control, Clinical, and Derived Groups

Abstract: Although recent findings have indicated that a portion of college students presenting for psychoeducational evaluations fail validity measures, methods for determining the validity of cognitive test results in psychoeducational evaluations remain under-studied. In light of this, data are needed to evaluate utility of validity indices in this population and to provide base rates for students meeting research criteria for malingering and to report the relationship between testing performance and the level of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Larrabee (2014) provided evidence that data from earlier publications (Larrabee 2003, 2009) show lower FPRs than predicted by either independent or correlated binomial models, and that other data (Pearson, 2009; Schroeder & Marshall, 2011; Victor, Boone, Serpa, Buehler, & Ziegler, 2009) have significantly lower FPRs than the Berthelson simulations. On the other hand, Berthelson and colleagues’ simulation data are very similar to both the empirical data of Pella and colleagues (2012), and to the empirical data of Davis and Millis (2014), as shown below. We examine details of these comparisons because they raise multiple substantive concerns about both the underlying assumptions and some of the interpretations of the data.…”
Section: Empirical Data On Pvt Failure Rates and Comparisons With Thesupporting
confidence: 58%
See 1 more Smart Citation
“…Larrabee (2014) provided evidence that data from earlier publications (Larrabee 2003, 2009) show lower FPRs than predicted by either independent or correlated binomial models, and that other data (Pearson, 2009; Schroeder & Marshall, 2011; Victor, Boone, Serpa, Buehler, & Ziegler, 2009) have significantly lower FPRs than the Berthelson simulations. On the other hand, Berthelson and colleagues’ simulation data are very similar to both the empirical data of Pella and colleagues (2012), and to the empirical data of Davis and Millis (2014), as shown below. We examine details of these comparisons because they raise multiple substantive concerns about both the underlying assumptions and some of the interpretations of the data.…”
Section: Empirical Data On Pvt Failure Rates and Comparisons With Thesupporting
confidence: 58%
“…First, he suggests that the empirical data (N = 478, college students with no incentive) from Pella and colleagues (Pella, Hill, Shelton, Elliott, & Gouvier, 2012), which are highly consistent with the Berthelson et al simulations, are overestimates. The first argument is that the PVTs used were not really independent, and indeed many were derived from the same underlying tests (e.g., Digit Span).…”
Section: Empirical Data On Pvt Failure Rates and Comparisons With Thementioning
confidence: 84%
“…However, participants had no overt incentive for poor effort, as they had been screened for any litigation and on-going chronic pain. Previous studies have suggested that participants without overt incentives for poor effort only fail standardized effort tests in a small proportion of cases (Kemp et al, 2008; Pella et al, 2012). This could be due to there being no difference in effort in these groups, due to the difference being so slight that it is not detectable, or due to the standardized tests not being suitable for detecting effort in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Probable malingering in psychoeducational contexts was estimated to be 596577J ADXXX10.1177/1087054715596577Journal of Attention DisordersHirsch and Christiansen research-article2015 1 Philipps University Marburg, Germany around 10% (Pella, Hill, Shelton, Elliott, & Gouvier, 2012). In contrast, the possibility of malingering in the context of ADHD has long been ignored (Alfano & Boone, 2007).…”
Section: Introductionmentioning
confidence: 99%